A scoping review on the use of telerehabilitation in physiotherapy in low and middle income countries - Ndzamba, Bonginkosi (Division of Clinical Pharmacology, 2025)
Introduction: Ethambutol is a bacteriostatic drug, administered as part of a fixed-dose combination regimen for the treatment of tuberculosis (TB). Individuals with comorbid HIV have reported reduced serum concentrations of ethambutol. We aimed to evaluate the pharmacokinetics of ethambutol in individuals with both drug-susceptible TB and HIV, identify covariates that influence ethambutol pharmacokinetics, and evaluate the current World Health Organization's (WHO) ethambutol dosing recommendations. Method: We used pharmacokinetic data from the TB-HAART open-label trial that investigated the outcomes of individuals with dual TB and HIV infections treated with first-line anti-TB drugs and antiretroviral therapy (ART). Modelling and simulation was performed using nonlinear mixed-effects modelling in the software NONMEM®. Results: A two-compartment disposition model with transit absorption best fitted the pharmacokinetic data. Allometry using fat-free mass and weight best scaled disposition parameters for body size for the final model. The typical clearance of ethambutol was 34.8 L/h. The Antib-4® formulation of ethambutol showed a 27.8% reduction in bioavailability and a 37.1% increase in mean transit time compared to the e-275 Rifafour® formulation. Creatinine clearance, presence of ART from day 13, and CD4+ T-cell count were also tested but did not improve the model fit. Our simulations showed that, with the current WHO fixed-dose combination regimen, individuals with weight 55 kg weight bands. Therefore, to balance exposures we proposed an additional 275 mg ethambutol dose. Similarly, our simulations suggest that the multidrug-resistant TB WHO 400 mg strength under-exposes patients with weight <54.9 kg had lower exposure to ethambutol 275 mg tablet strength than those in >55 kg weight bands. Therefore, to balance exposures we proposed an additional 275 mg ethambutol dose. Similarly, our simulations suggest that the multidrug-resistant TB WHO 400 mg strength under-exposes patients with weight <46.9 kg, which could be addressed by increasing the dose by 400 mg. Conclusion: We developed a model for ethambutol and observed that different formulations of ethambutol affected its bioavailability and absorption. Our simulation results indicated that individuals weighing less than 55 kg with drug-susceptible TB and those weighing less than 46 kg with multidrug-resistant TB are at risk of being underdosed. To ensure improved therapeutic outcomes for these individuals, a proposed dose optimization is a more effective solution.